Targeting Purine Biosynthesis for Antibacterial Drug Design - Modi G.; Chacko S.; Hedstrom L. (My University, 2025)
The purine nucleotide pathways are tempting targets for antibiotic design. However, the vulnerability of these potential targets is questioned by the potential redundancy of the de novo biosynthesis and salvage pathways questions. Indeed, genetic experiments suggest that the vulnerability of these enzymes varies with pathogen and environmental niche. More target validation in the form of conditional knockouts could provide the confidence needed to launch drug discovery efforts. The purine conversion pathways are required for both de novo synthesis and salvage, suggesting that these four enzymes, adenylosuccinate synthetase, adenylosuccinate lyase, IMP dehydrogenase and GMP synthetase, are the better candidates. Even here the similarity of the active sites in pathogen and host enzymes can be discouraging. To date, only inhibitors of IMP dehydrogenase have been pursued with a significant effort. Mammalian and bacterial IMP dehydrogenases have dramatically different cofactor binding sites that can be exploited to identify selective inhibitors. Antibacterial activity has been reported against Gram positive pathogens and Mycobacterium tuberculosis, but no compound has achieved the critical milestone of activity in an animal model of infection. © The Royal Society of Chemistry 2017.